Pemberdayaan Guru sebagai Relawan untuk Mencegah Kekerasan Terhadap Anak dan Perempuan di Malaysia: Empowering Teachers as Volunteers to Prevent Violence Against Children and Women in Malaysia - Erna Risnawati; Siti Utami Dewi Ningrum; Muktia Pramitasari; Mani Festati Broto; Anto Hidayat; Juppri Bacotang (Amalee: Indonesian Journal of Community Research and Engagement, 2026)
Violence against children and women remains a significant concern within Indonesian migrant worker communities in Sabah, Malaysia, especially in plantation areas where access to protection services and reporting systems is limited. Teachers at Community Learning Centers (CLCs) are in a strategic position to help prevent and respond to such cases, yet many lack adequate knowledge and skills. This community service program aimed to strengthen teachers’ capacity as violence prevention volunteers. The program was implemented by Universitas Terbuka in collaboration with Universiti Malaysia Sabah and FGV Holdings Berhad, involving 45 teachers from nine CLCs. Participants attended a three-day training program covering violence prevention, child protection, cyberbullying awareness, reporting procedures, case management, and educational media development. Evaluation results showed substantial improvement in participants’ understanding, with knowledge levels increasing from around 60% before training to over 90% afterward. The program also established a Reading Corner and educational resources to support sustainable violence prevention efforts in vulnerable communities.